2005
DOI: 10.1142/s0218195905001828
|View full text |Cite
|
Sign up to set email alerts
|

A Lower Bound for Lebesgue's Universal Cover Problem

Abstract: In the following we show that any convex set that contains a congruent copy of any set of diameter one (universal cover) has area at least 0.832. This considerably improves the lower bound for Lebesgue's universal cover problem, using a combination of computer search and geometric bounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…In recent years computational methods have increasingly been employed to attack geometric questions. For example, Brass and his student Sharifi [3] used a grid search numerical method to improve the known lower bound for the Lebesgue Universal Cover problem. In this article we employ numerical convex optimization to reduce the known upper bound for α 2 by nearly 1.7 per cent.…”
Section: A Smaller Covermentioning
confidence: 99%
“…In recent years computational methods have increasingly been employed to attack geometric questions. For example, Brass and his student Sharifi [3] used a grid search numerical method to improve the known lower bound for the Lebesgue Universal Cover problem. In this article we employ numerical convex optimization to reduce the known upper bound for α 2 by nearly 1.7 per cent.…”
Section: A Smaller Covermentioning
confidence: 99%
“…By Lemma 1 both connected components, denoted by C 1 and C 2 , are of diameter at most 1, so Jung's theorem [15,28] Note that we used a bit wastefully the Jung enclosing balls. The universal cover problem, first stated in a personal communication of Lebesgue in 1914, asks for the minimum area A of a convex set U containing a congruent copy of any planar set of diameter 1, see [8]. For the currently best known bounds 0.832 ≤ A ≤ 0.844 and generalizations to higher dimensions we refer the interested reader to [7,Section 11.4].…”
Section: Bounds For L D (N)mentioning
confidence: 99%
“…Lebesgue's problem was first studied by Pál [8], who found that the area of a smallest universal cover is at least 0.8257 and at most 0.8454. Both bounds were improved by several authors, the current best upper bound is around 0.844 [3], the best lower bound is around 0.832 [5], so the problem is still open.…”
Section: Introductionmentioning
confidence: 99%